A controllable thermal-sensitivity separator with an organic–inorganic hybrid interlayer for high-safety lithium-ion batteries. (15th February 2021) - Chen, Hui; Fang, Youlong; Liu, Xingwei; Jiang, Xiaoyu; Zhong, Faping; Yang, Hanxi; Ai, Xinping; Cao, Yuliang
Abstract : The PAN/EVA@SiO2 /PAN (PESP) separator fabricated by electrospinning approach exhibits a proper shutdown function at approximately 120 °C, which can greatly improve the safety of lithium-ion batteries. Abstract : A bifunctional organic–inorganic hybrid separator (PAN/EVA@SiO2 /PAN, PESP) for lithium-ion batteries was successfully fabricated by a facile electrospinning approach. This PESP separator shows an appropriate shutdown behavior at 120 °C by incorporating a suitable amount of SiO2 into the EVA and can maintain dimensional integrity at 200 °C because of the high thermal stability of PAN as a supporting scaffold. Besides, the graphite/LiFePO4 full cell using the PESP separator exhibits enhanced rate performance as a consequence of the good electrolyte wettability of the separator compared to the traditional Celgard separator. These attractive characteristics make the PESP membrane act as a promising separator for next-generation high-safety batteries.